Chlamydial Plasmid-Encoded Virulence Factor Pgp3 Neutralizes the Antichlamydial Activity of Human Cathelicidin LL-37 - Hou, Shuping (Infect Immun, 2015)
Chlamydia trachomatis infection in the lower genital tract can ascend to and cause pathologies in the upper genital tract, potentially leading to severe complications, such as tubal infertility. However, chlamydial organisms depleted of plasmid or deficient in the plasmid-encoded Pgp3 are attenuated in ascending infection and no longer are able to induce the upper genital tract pathologies, indicating a significant role of Pgp3 in chlamydial pathogenesis. We now report that C. trachomatis Pgp3 can neutralize the antichlamydial activity of human cathelicidin LL-37, a host antimicrobial peptide secreted by both genital tract epithelial cells and infiltrating neutrophils. Pgp3 bound to and formed stable complexes with LL-37. We further showed that the middle region of Pgp3 (Pgp3m) was responsible for both the binding to and neutralization of LL-37, suggesting that Pgp3m can be targeted for attenuating chlamydial pathogenicity or developed for blocking LL-37-involved non-genital-tract pathologies, such as rosacea and psoriasis. Thus, the current study has provided significant information for both understanding the mechanisms of chlamydial pathogenesis and developing novel therapeutic agents.